Development Of Patriotism In Students Through History Teaching: Directions And Assessment Criteria - Djumaniyozov Ikrambek Ismailovich (Periodica Journal, 2024)
The article discusses the stages of forming a sense of patriotism among students through teaching history, the principles of selection and presentation of educational material, teaching such knowledge and skills as how to work with the information provided, how and where to look for information, how to compare, what to base the comparison on. discusses the stages of forming a sense of patriotism among students through teaching history, the principles of selection and presentation of educational material, teaching such knowledge and skills as how to work with the information provided, how and where to look for information, how to compare, what to base the comparison on
Keywords: Patriotism; History Lessons; Concepts On The Topic; Interpretation